Comparison of Cold-Knife Conization versus Loop Electrosurgical Excision for Cervical Adenocarcinoma In Situ (ACIS): A Systematic Review and Meta-Analysis - Jiang, Yanming (PLoS One, 2017)
OBJECTIVE: The objective of this systematic review was to conduct a more comprehensive literature search and meta-analysis of original studies to evaluate the efficacy and safety of the loop electrosurgical excision procedure (LEEP) versus cold-knife conization (CKC) in conservative surgical treatment of cervical adenocarcinoma in situ (ACIS) for women who have not completed childbearing. METHODS: Systematic searches were conducted in the PUBMED, EMBASE, Cochrane, and China National Knowledge Infrastructure (CNKI) databases to identify all potential studies involving patients with ACIS treated with LEEP versus CKC published until December 2015. RESULTS: Eighteen retrospective studies were included in this systematic review. All the 18 included studies reported the rate of positive margins, and the results of the individual studies varied. The positive margins were 44% (267/607) after LEEP and 29% (274/952) after CKC. The pooled meta-analysis exhibited significantly different outcome (RR, 1.55; 95% CI, 1.34–1.80, P<0.00001) without significant heterogeneity (P = 0.34). The residual rate following LEEP was 9.1% (17/186) and 11% (39/350) after CKC in re-cone or hysterectomy cases. Recurrent ACIS following LEEP was reported in 10 of 142 (7.0%) cases compared to 10 of 177 (5.6%) cases following CKC. There were no significant differences in the residual rate (RR, 1.02; 95% CI, 0.60–1.72, P = 0.95) or recurrence rate (RR, 1.13; 95% CI, 0.46–2.79; P = 0.79) between the two procedures. CONCLUSIONS: The present systematic review demonstrates that both LEEP and CKC are safe and effective for the conservative treatment of ACIS. LEEP appears to be as equally effective as CKC regarding the residual and recurrence rates. Due to the findings showing that LEEP achieves comparable oncologic outcomes with fewer obstetric complications to that of CKC, LEEP may be the preferred option in patients whose fertility preservation is important. However, further prospective studies with a larger sample size and longer follow-up periods are needed to establish the superiority of either procedure.